Experimental and Theoretical Analysis of the Influence of Different Linker Molecules in Imidazolate Frameworks Potsdam (IFP-n) on the Separation of Olefin-Paraffin Mixtures - Hovestadt, Maximilian; Bendt, Stephan; Mondal, Suvendu Sekhar; Behrens, Karsten; Reif, Florian; Dopken, Merle; Holdt, Hans-Juergen; Keil, Frerich J.; Hartmann, Martin (Langmuir, 2017)
Four metal organic frameworks with similar topology but different chemical environment inside the pore structure, namely, IFP-1, IFP-3, IFP-5, and IFP-7, have been investigated with respect to the separation potential for olefin paraffin mixtures as well as the influence of the different linkers on adsorption properties using experiments and Monte Carlo simulations. All IFP structures show a higher adsorption of ethane compared to ethene with the exception of IFP-7 which shows no selectivity in breakthrough experiments. For propane/propane separation, all adsorbents show a higher adsorption for the olefin. The experimental results agree quite well with the simulated values except for the IFP-7, which is presumably due to the flexibility of the structure. Moreover, the experimental and simulated isotherms were confirmed with breakthrough experiments that render IFP-1, IFP-3, and IFP-5 as suitable for the purification of ethene from ethane.